Incremental shuttle walking test to assess functional capacity in cardiac rehabilitation: a narrative review. (2nd May 2022) - Pepera, Garyfallia; Sandercock, Gavin RH
Abstract : Background/Aims: Low functional capacity has been recognised to be the most important predictor of overall mortality compared to all other cardiovascular risk factors in patients with cardiovascular disease. Walk tests, such as the incremental shuttle walking test and the 6-Minute Walk Test, are used to assess functional capacity in patients, the effectiveness of a cardiac rehabilitation programme and the prognosis of cardiovascular diseases. The aim of this review was to provide a narrative review of the literature and identify the key features of the incremental shuttle walking test as a measure of functional capacity testing in cardiac rehabilitation patients. Methods: The PubMed, MEDLINE, Elsevier and Google Scholar databases were searched for relevant scientific articles published up to March 2021 with no restriction on start day. The key words defined by researchers were 'incremental shuttle walking test', 'exercise test', 'functional capacity', 'cardiovascular disease', 'cardiac rehabilitation', 'reliability' 'prediction; 'walk tests'. A final set of 31 articles was included in this narrative review. Results: Evidence-based findings suggest that the incremental shuttle walking test is a valid, reliable, sensitive, useful tool for detecting and predict cardiorespiratory capacity. Conclusions: Clinicians can be confident that they can use the incremental shuttle walking test to monitor changes in functional capacity in patients with cardiovascular disease.